2016
DOI: 10.1155/2016/2050796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peripapillary Nerve Fiber Layer after Dexamethasone Implantation (Ozurdex) in Branch Retinal Vein Occlusions

Abstract: Purpose. To evaluate the peripapillary retinal nerve fiber layer (RNFL) thicknesses of patients treated with intravitreal Ozurdex implant due to branch retinal vein occlusion (BRVO) related macular edema (ME). Methods. Thirty-three eyes of 33 patients treated with Ozurdex implant due to ME associated with BRVO were included in the study. Ophthalmic examinations including determination of best corrected visual acuity (BCVA), measurement of intraocular pressure (IOP), and central macular thickness (CMT) and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…MRNFL thickness was inversely correlated with IOP ( p = 0.01, r = −0.40), suggesting that even though in 68.97% of patients IOP increased to levels below 21 mmHg, this increase degree may be sufficient to negatively affect the optic nerve. Our results regarding RNFL thickness corroborate the findings of Bulut et al, 21 that demonstrated a significant decrease in MRNFL and IRNFL thickness measured by OCT 6 months after intravitreal injection of dexametasone implant (104.10 ± 11.10 vs 101.10 ± 10.4, p < 0.001; 130.7 ± 17.50 vs 126.40 ± 20.10, p < 0.001, respectively), but contradict the study of Wannamaker et al, 22 that did not find differences in RNFL thickness measured by OCT regardless of IOP increase degree or glaucoma history. Aditionally, in our study there was an increase in vertical C/D ratio from 0.58 ± 0.06 to 0.60 ± 0.14 up to 6 months after the IVT of TA (mean 4.90 ± 1.06 months), which was also correlated with IOP increase ( p = 0.04, r = 0.28).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…MRNFL thickness was inversely correlated with IOP ( p = 0.01, r = −0.40), suggesting that even though in 68.97% of patients IOP increased to levels below 21 mmHg, this increase degree may be sufficient to negatively affect the optic nerve. Our results regarding RNFL thickness corroborate the findings of Bulut et al, 21 that demonstrated a significant decrease in MRNFL and IRNFL thickness measured by OCT 6 months after intravitreal injection of dexametasone implant (104.10 ± 11.10 vs 101.10 ± 10.4, p < 0.001; 130.7 ± 17.50 vs 126.40 ± 20.10, p < 0.001, respectively), but contradict the study of Wannamaker et al, 22 that did not find differences in RNFL thickness measured by OCT regardless of IOP increase degree or glaucoma history. Aditionally, in our study there was an increase in vertical C/D ratio from 0.58 ± 0.06 to 0.60 ± 0.14 up to 6 months after the IVT of TA (mean 4.90 ± 1.06 months), which was also correlated with IOP increase ( p = 0.04, r = 0.28).…”
Section: Discussionsupporting
confidence: 93%
“…One month after the IVT, IOP increased in 86.21% of our patients. Mean IOP increase was 2.39 ± 0.80 mmHg, which was lower than Nicolò et al 8 and higher than Zając-Pytrus et al 20 and Bulut et al 21 studies (mean 3.13, 2 and 0.80 mmHg, respectively). In 80% of our patients with IOP increase, IOP remained equal to or below 21 mmHg without medication.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Six studies investigated RNFL-thickness at a specific point in time during follow-up. Bulut et al found that 6 months after dexamethasone implant the average RNFL-thickness had been reduced from 104.1 ± 11.1 µm to 101.1 ± 10.4 µm (P < 0.001) 37 . Four of the studies (124 eyes) were included in our meta-analysis for anti-VEGF.…”
Section: Intravitreal Injection Of Anti-vegf or Dexamethasone Implantmentioning
confidence: 98%
“…Ayar et al [ 31 ], evaluated the effects of intravitreal DEX implant on RNFL thickness in patients with BRVO in a 6-month period and reported that there were no significant changes in mean RNFL values postoperatively compared to baseline values in all quadrants. On the other hand, Bulut et al [ 32 ], reported that the mean IOP was significantly increased from baseline at 1st day, 1st week, and 1st month visits, and inferior quadrant peripapillary RNFL thickness was significantly reduced at the 6th month compared to at baseline in patients with BRVO-related macular edema. Similarly, we also determined a significant decrease in inferior peripapillary RNFL thickness in both groups at the end of the 6th month.…”
Section: Discussionmentioning
confidence: 99%